Analysis of Quality and Quantity of Work Performed by Village Apparatus in Terms of Competence: Case Study in Kebumen Village, Banyumas - Imanda Naufal Yuswono; Achmad Sudjadi; Najmudin Najmudin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The village is one of the jurisdictions of the legal community which has the boundaries of the territory authorized to regulate and administer government affairs. In this case the role of village government is very important because it concerns the service to the community. The maximum productivity of the village apparatus is one of the things that makes the government's goal achievable. This study uses a descriptive method with a qualitative approach, conducting direct interviews with Kebumen Village officials and the people in that village. Based on research and analysis of performance indicators quality of work and quantity of work of the Kebumen Village Apparatus in carrying out their duties is considered not optimal, especially when there are still violations of work discipline, the violations related to working hours. Some factors inhibiting the performance of village apparatus in the form of a lack of number of village apparatus and a lack of development quality of human resources in Kebumen Village Apparatuses. It is necessary to make efforts to develop human resources for Kebumen Village Apparatuses to improve technical, theoretical and work discipline capabilities to improve apparatus performance Kebumen village.